Quad rugby: A strength and conditioning program for the elite athlete - Gulick, D.; Berge, B.; Borger, A.; Edwards, J.; Rigterink, J. (Strength and Conditioning Journal, 2006)
Disabled sports are a recreational outreach for individuals who have experienced injuries or have physical limitations.Quad rugby is a sport for individuals with spinal cord injury, and it has grown exponentially in popularity. Disabled sports have recently expanded to the national and international levels. With increasing competition, the physical demands have been elevated to a new level. Athletes participating in disabled sports need comprehensive strength and conditioning programs to compete at high levels.